IMPROVING THE MANAGEMENT OF PUD WATER AND WASTEWATER BASED DEVELOPMENT PROGRAMME - and (Municipal economy of cities (Technical science), 2013)
The possibility of improving the functioning utilities of water and wastewater using development programs, taking into account the characteristic features of water supply and sanitation.